2023
DOI: 10.3390/pathogens12030395
|View full text |Cite
|
Sign up to set email alerts
|

Type I Cystatin Derived from Fasciola gigantica Suppresses Macrophage-Mediated Inflammatory Responses

Abstract: There is an inverse relationship between the high incidence of helminth infection and the low incidence of inflammatory disease. Hence, it may be that helminth molecules have anti-inflammatory effects. Helminth cystatins are being extensively studied for anti-inflammatory potential. Therefore, in this study, the recombinant type I cystatin (stefin-1) of Fasciola gigantica (rFgCyst) was verified to have LPS-activated anti-inflammatory potential, including in human THP-1-derived macrophages and RAW 264.7 murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…All collected fractions were run on 12.5% SDS-PAGE and stained with Coomassie brilliant blue G-250 for evaluation. At the same time, the recombinant thioredoxin (rTrx) was produced from BL21(DE3) E. coil containing pET32a(+) and purified under native conditions as previously described 17 , 35 , 36 . The purified r Fg RXRα-A + Trx and rTrx were transferred to a micro-dialysis bag (Sigma-Aldrich, St. Louis, MO, USA) for dialysis against PBS, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…All collected fractions were run on 12.5% SDS-PAGE and stained with Coomassie brilliant blue G-250 for evaluation. At the same time, the recombinant thioredoxin (rTrx) was produced from BL21(DE3) E. coil containing pET32a(+) and purified under native conditions as previously described 17 , 35 , 36 . The purified r Fg RXRα-A + Trx and rTrx were transferred to a micro-dialysis bag (Sigma-Aldrich, St. Louis, MO, USA) for dialysis against PBS, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Proteinase inhibitors are of interest as they not only regulate the proteinases of the parasite but also those of the host. A few cystatins have been molecularly characterized in the trematodes Schistosoma sp., Fasciola sp., and Clonorchis sinensis , for example, two Fasciola gigantica cystatins, both classified as type 1 cystatin, were found to be involved with regulating intracellular cysteine proteinase activity and protecting against extracellular proteolytic processes [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. From our previous study of type 3 multi-domain cystatin in Fasciola gigantica , we found that processed cystatin domains inhibited both parasite and mammalian cysteine proteinases.…”
Section: Introductionmentioning
confidence: 99%